Precursors to Cholangiocarcinoma - Tomas Hucl (Gastroenterology Research and Practice)
Cancers of the biliary tract include intra- and extrahepatic cholangiocarcinomas and gallbladder cancer. Biliary tract cancers are diseases with unfavorable prognoses. In recent years, several lesions have been described as precursors that precede biliary cancers. They include flat and microscopic lesions known as biliary intraepithelial neoplasia, macroscopic and tumor-forming intraductal papillary biliary neoplasia, intraductal tubular neoplasia, and mucinous cystic neoplasm of the bile duct. These conditions are rarely diagnosed, while their natural history and progression to cancer have yet to be adequately characterized. This review examines the epidemiology, pathology, molecular biology, diagnosis, and therapy of these various precursors. Further research is required if we are to better understand this evolving field and improve the prevention and early detection of bile duct cancer.